CARACTÉRISTIQUES SOCIO-ÉPIDÉMIOLOGIQUES ET ÉVOLUTIVES DES INTOXICATIONS AIGUËS AU MAROC : CAS DE LA RÉGION DE L’ORIENTAL - Hajar, Rebgui; Hinde, Hami; Lahcen, Ouammi; Fatine, Hadrya; Abdelmajid, Soulaymani; Rachida, Soulaymani-Bencheikh; Abdelghani, Mokhtari (European Scientific Journal, ESJ, 2013)
A retrospective epidemiological study concerning 4 098 cases of acute poisoning registered in the region of the Oriental between January, 2007 and December, 2011 was realized. The data have been collected by The Moroccan Poison Control and Drug Monitoring Center (centre anti-poison et de pharmacovigilance "CAPM"). Such study aims to reduce morbidity and mortality resulting from poisoning in the oriental region, through the description of the major epidemiological characteristics associated with it. The results showed the average age of the intoxicated 24.7±16.4 years. The poisonings in this region concerned mainly the adults whose age is understood between 20 years and 74 years (56.9 %). The lethality rate was more important at the elderly Person ([> 75]) (2.62 %). The female prevailed with (62.8%), the sex ratio (F/M) being 1.68. The frequencies of the highest ﻿poisonings were recorded in the urban middle with 90.1 %. The poisonings were accidental in 76.6 % of the cases. The clinical state of the patients was for the greater part symptomatic (74.9 %). The most incriminated products were drugs with 29.6 % of the cases. Among 3 453 patients for whom the evolution was known, 3 407 cases had favorably evolved, 46 had died, that is a lethality of 1.3 %. The study of the effect of the studied parameters on the evolution of the health status of patients has led to progress as follows: The origin (urban, rural) and the clinical state (symptomatic, asymptomatic) presented a significant association with the evolution of the patients: The Odds ratio was respectively, (OR=2.33, p=0.028) and (OR=6.51, p=0.001). To reduce the incidence of acute accidental and intentional poisonings, prevention and improvement of socio-economic conditions remain the treatment of choice.